Effect of Therapeutic Ionizing Radiation on Implantable Electronic Devices: Systematic Review and Practical Guidance. (4th August 2016) - TAJSTRA, MATEUSZ; GADULA‐GACEK, ELZBIETA; BUCHTA, PIOTR; BLAMEK, SLAWOMIR; GASIOR, MARIUSZ; KOSIUK, JEDRZEJ
Systematic Review and Practical Guidance: Cardiac implantable electronic devices (CIEDs) have been in use for over 50 years and their therapeutic value is undisputable. With the rapidly aging population, it is estimated that the number of CIEDs will grow dramatically over the next 2 decades. Given these predictions, the topic of management of concomitant conditions associated with older age becomes more relevant than ever. In particular, the number of patients with an implanted CIED diagnosed with cancer is expected to rise by about 70%, from 14 million in 2012 to 22 million within the next 2 decades. Treatment of most of these tumors and tumor metastases requires radiation therapy. However, the necessary high doses of radiation can potentially interact with the function, longevity, and integrity of the CIEDs and/or cause harm to the patient. The impact of an absence of clear therapeutic guidelines for oncology patients with CIEDs who should undergo radiation therapy is vast; and due to the fear of possible complications related to device failure, many of these patients may not be treated adequately to their needs, which can strongly affect their prognosis. This article summarizes the available data on the management of patients with CIEDs undergoing radiotherapy. It systematically presents possible causes and consequences of direct and scattered radiation on CIEDs, highlights possible complications that may occur during this kind of treatment, and provides practical guidance for this challenging real life clinical setting.